Local Name Authorities and Linked Data: The Landscape - Craft, Anna R. (Serials review, 2019)
Name authority control-the process of selecting and maintaining a set of headings or access points for named entities-brings consistency to names in online systems and can help users locate needed items and identify related materials. Linked data provides the opportunity to extend name authority data sets and make them available to wider audiences. This column seeks to provide an overview of the landscape of local name authority projects using linked data, along with practices, challenges, and other considerations in this area.